Peran Supporting Agency Komite Sekolah dalam Pembiayaan Pendidikan - Muhammad Ghozali; Eka Ariskawanti (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Weak allocation and procurement of funds in educational institutions, affects the educational process. The reason is that the budget is the main means of supporting and carrying out activities in education. The school committee is an organizational body that is held to support solutions, provide considerations, and complete the results of coordination through its role in communicating the institution by providing a positive image to the community and partners. One of the committee's roles as a supporting agency is to support procurement activities and the allocation of school budgets. The research approach used is descriptive qualitative, which then uses interview and observation data analysis techniques. The purpose of the study focused on social conditions in the role of the school committee's supporting agency in financing education. Research that has been carried out at Madrasah Ibtidaiyah Swasta Al-Ittihadiyah Al-Islamiyah (MIS AIAI) identified the following results: 1) the role of mobilizing the education financing budget with good management functions, 2) the committee carries out monitoring and evaluation to determine the level of effectiveness of the implementation of activities carried out, 3) Monitoring and evaluation is carried out by the committee (MIS AIAI) by holding committee meetings between the community and the school, and 4) The role in organizing the education budget is also pursued through visits to people who are in the capable category to support the education process.